FARMING IN FISHING COMMUNITIES IN JAPAN CASE STUDY IN THE SANRIKU REGION - Keiko Yoshino; Tatsuya Kawaguchi (Journal of Asian Rural Studies, 2020)
Farming in fishing communities has been little investigated in Japan up to now. Agriculture and fisheries are sectionalized and treated as different industries, and the farming situations in fishing households have not been studied statistically since 2003. For this paper, the ways in which farming in Japanese fishing communities has changed was investigated. Farming in fishing communities will be described, looking at cases from the Sanriku region, and the meaning of farming in fishing communities will be explored. According to the fisheries census, 68% of fishing households owned farmland in 1953. In 2003, only 11% of fishing households were also engaged in farming (hereinafter referred to as fishing-cum-farming households). In the Sanriku region, fishing-cum-farming households were more than 80% of farming households in 1968. By 2003, the percentages had decreased to 15% and below. For fishing-cum-farming households, whether one owns paddy fields or not is significant because rice has been the dominant staple food in Japan. It was fortunate for fishermen to live in communities where paddies could be cultivated, but paddy fields were owned by a limited number of households. The total area of paddy fields increased as the northern limit of paddy production was extended.